Cell-Wall-Degrading Enzymes Required for Virulence in the Host Selective Toxin-Producing Necrotroph Alternaria alternata of Citrus - Ma, Haijie; Zhang, Bin; Gai, Yunpeng; Sun, Xuepeng; Chung, Kuang-Ren; Li, Hongye (Frontiers in Microbiology, 2019)
The necrotrophic fungal pathogen Alternaria alternata attacks many citrus cultivars, causing brown spot disease. Its pathogenic capability depends primarily on the production of host-selective ACT toxin. In the current study a Ste12 transcription factor was characterized to be required for conidial formation and the production of cell-wall-degrading enzymes (CWDEs) in the tangerine pathotype of A. alternata. The Ste12 deficiency strain (∆Ste12) retained wild-type growth, ACT toxin production, and sensitivity to oxidative and osmotic stress. However, pathogenicity tests assayed on detached Dancy leaves revealed a marked reduction in virulence of ∆Ste12. Transcriptome and quantitative RT-PCR analyses revealed that many genes associated with Carbohydrate-Active Enzymes (CAZymes) were downregulated in ∆Ste12. Two cutinase-coding genes (AaCut3 and AaCut7) regulated by Ste12 were individually and simultaneously inactivated. The AaCut3 or AaCut7 deficiency strain unchanged in cutinase activities and incited wild-type lesions on Dancy leaves. However, the strain carrying an AaCut3 AaCut7 double mutation produced and secreted significantly fewer cutinases and incited smaller necrotic lesions than wild type. Not only is the host-selective toxin produced by A. alternata required for fungal penetration and lesion formation, but so too are CWDEs required for full virulence. Overall, this study expands our understanding of how A. alternata overcomes citrus physical barriers to carry out successful penetration and colonization.